STRATEGI PEMASARAN BARANG DAN JASA PERUSAHAAN MELALUI MEDIA IKLAN - Martiman, - (Jurnal Ilmiah Widya, 2014)
The marketing strategy needed to offer goods and services as a commodity of companies to the market. One way used by of companies to inform products to market by using advertising. The purpose of this paper is to examine: (1) micro marketing management, (2) the development of a marketing strategy to be able to meet some needs of a wider audience of consumers, (3) the factors of an effective marketing strategy, (4) pricing strategies. The method used literature review is exploratory which explorative descriptive approaches. It can be concluded that: (1) goods and services marketing strategy through media advertising is required to inform the company's products and services to market.(2) in the marketing of goods and services, the company sees the consumer behavior is influenced by cultural factors, social factors, and the degree of personal and psychological, (3) effective marketing requires the phasing plan, the concept of strategy of market segmentation, strategy and marketing planning is good and ripe application, brand, label and packaging as the attractiveness of the market. One of the components of marketing to be reckoned with either is the price of the product. (4) Pricing strategies need to pay attention to factors internal and external that affected it, such as: cultural factors, social factors, levels, personality and psychological factors, it requires attention because consumer behavior is the basis of the formation of the buying decision process.